Local Wisdom-Based Social Sanctions in Indonesian Criminal Law: A Legal-Political Analysis - Muhammad Topan; Erniyati, Tiya (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Indonesian criminal law reform has shifted from a retributive orientation toward a more restorative and socially responsive approach, as reflected in the recognition of living law under Law Number 1 of 2023 on the National Criminal Code. However, local wisdom-based social sanctions, which have long functioned as community-based restorative mechanisms, remain absent from explicit codification in the national penal system. This normative gap raises an important legal-political question concerning the possibility of institutionalizing such sanctions through Regional Regulations (Peraturan Daerah) without violating constitutional principles, national criminal law, and human rights standards. This study aims to examine the legal-political basis for such institutionalization and to formulate the normative limits and regulatory model that should govern it. The study employs normative legal research using statutory, conceptual, philosophical, and socio-legal approaches. The findings show that local wisdom-based social sanctions have received indirect normative recognition through restorative justice mechanisms in Law Number 11 of 2012, Prosecutor Regulation Number 15 of 2020, Supreme Court Regulation Number 1 of 2024, and the social work punishment policy in Law Number 1 of 2023. The study also finds that Regional Regulations may serve as derivative policy instruments to accommodate public apology, community service, moral restitution, and customary obligations, provided that they remain participatory, non-repressive, accountable, and consistent with Pancasila and constitutional guarantees. Such institutionalization is legally possible, but it must be limited to restorative measures aimed at restoring social harmony and guiding constitutionally compliant local regulation.